Synthesis of functionalized diazocines for application as building blocks in photo- and mechanoresponsive materials - Moormann, Widukind; Langbehn, Daniel; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2019)
Seven symmetrically 3,3’-substituted diazocines were synthesized. Functional groups include alcohol, azide, amine and vinyl groups, which are suitable for polymer synthesis. Upon irradiation at 385 and 530 nm the diazocines perform a reversible, pincer-type movement switching the 3,3’-distance between 6.1 Å (cis, stable isomer) and 8.2 Å (trans, metastable isomer). Key reactions in the synthesis are an oxidative C–C coupling of 2-nitrotoluenes (75–82% yield) and a reductive ring closure to form the diazocines (56–60% yield). The cyclization of the dinitro compound to the azo compound was improved in yield and reproducibility, by over-reduction to the hydrazine and reoxidation to the azo unit. In contrast to 3,3’- and 4,4’-diaminodiazocine, which have been implemented in macromolecules for conformation switching, our compounds exhibit improved photophysical properties (photostationary states, separation of absorption bands in the cis and trans configuration). Hence they are promising candidates as molecular switches in photo and mechanoresponsive macromolecules and other smart materials.
Keywords: bridged azobenzene; diazocine; mechanophor; oxidative C–C coupling; photochrome; reductive azo cyclization

(untitled) - Ikeda, T.; Mamiya, J.-i.; Yu, Y. (Angew. Chem., Int. Ed., 2007)

(untitled) - Davis, D. A.; Hamilton, A.; Yang, J.; Cremar, L. D.; Van Gough, D.; Potisek, S. L.; Ong, M. T.; Braun, P. V.; Martínez, T. J.; White, S. R.; Moore, J. S.; Sottos, N. R. (Nature, 2009)

(untitled) - Potisek, S. L.; Davis, D. A.; Sottos, N. R.; White, S. R.; Moore, J. S. (J. Am. Chem. Soc., 2007)

(untitled) - Kim, S.-J.; Reneker, D. H. (Polym. Bull., 1993)

(untitled) - Hosono, N.; Kajitani, T.; Fukushima, T.; Ito, K.; Sasaki, S.; Takata, M.; Aida, T. (Science, 2010)

(untitled) - Kim, C. B.; Wistrom, J. C.; Ha, H.; Zhou, S. X.; Katsumata, R.; Jones, A. R.; Janes, D. W.; Miller, K. M.; Ellison, C. J. (Macromolecules, 2016)

(untitled) - Yu, Y.; Nakano, M.; Ikeda, T. (Nature, 2003)

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Luo, Q.; Cheng, H.; Tian, H. (Polym. Chem., 2011)

(untitled) - Ryo, S.; Ishibashi, Y.; Murakami, M.; Miyasaka, H.; Kobatake, S.; Irie, M. (J. Phys. Org. Chem., 2007)

(untitled) - Corredor, C. C.; Huang, Z.-L.; Belfield, K. D.; Morales, A. R.; Bondar, M. V. (Chem. Mater., 2007)

(untitled) - Stellacci, F.; Bertarelli, C.; Toscano, F.; Gallazzi, M. C.; Zotti, G.; Zerbi, G. (Adv. Mater. (Weinheim, Ger.), 1999)

(untitled) - Pu, S.-Z.; Sun, Q.; Fan, C.-B.; Wang, R.-J.; Liu, G. (J. Mater. Chem. C, 2016)

(untitled) - Gossweiler, G. R.; Hewage, G. B.; Soriano, G.; Wang, Q.; Welshofer, G. W.; Zhao, X.; Craig, S. L. (ACS Macro Lett., 2014)

(untitled) - Celestine, A.-D. N.; Beiermann, B. A.; May, P. A.; Moore, J. S.; Sottos, N. R.; White, S. R. (Polymer, 2014)

(untitled) - Lee, C. K.; Beiermann, B. A.; Silberstein, M. N.; Wang, J.; Moore, J. S.; Sottos, N. R.; Braun, P. V. (Macromolecules, 2013)

(untitled) - Beiermann, B. A.; Davis, D. A.; Kramer, S. L. B.; Moore, J. S.; Sottos, N. R.; White, S. R. (J. Mater. Chem., 2011)

(untitled) - Klajn, R. (Chem. Soc. Rev., 2014)

(untitled) - Li, S.; Han, G.; Zhang, W. (Macromolecules, 2018)

(untitled) - Sell, H.; Näther, C.; Herges, R. (Beilstein J. Org. Chem., 2013)

(untitled) - Tellkamp, T.; Shen, J.; Okamoto, Y.; Herges, R. (Eur. J. Org. Chem., 2014)

(untitled) - Joshi, D. K.; Mitchell, M. J.; Bruce, D.; Lough, A. J.; Yan, H. (Tetrahedron, 2012)

(untitled) - Hammerich, M.; Schütt, C.; Stähler, C.; Lentes, P.; Röhricht, F.; Höppner, R.; Herges, R. (J. Am. Chem. Soc., 2016)

(untitled) - Siewertsen, R.; Neumann, H.; Buchheim-Stehn, B.; Herges, R.; Näther, C.; Renth, F.; Temps, F. (J. Am. Chem. Soc., 2009)

(untitled) - Schehr, M.; Hugenbusch, D.; Moje, T.; Näther, C.; Herges, R. (Beilstein J. Org. Chem., 2018)

(untitled) - Siewertsen, R.; Schönborn, J. B.; Hartke, B.; Renth, F.; Temps, F. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Moormann, W.; Langbehn, D.; Herges, R. (Synthesis, 2017)

(untitled) - Samanta, S.; Qin, C.; Lough, A. J.; Woolley, G. A. (Angew. Chem., 2012)

Photochromism: Molecules and Systems - Rau, H. (Azo Compounds, 2003)

(untitled) - Chaudhuri, N. K.; Ball, T. J. (J. Labelled Compd. Radiopharm., 1981)

(untitled) - Beyerman, H. C.; Bontekoe, J. S. (Proc. Chem. Soc., London, 1961)

(untitled) - Schlessinger, R. H.; Nugent, R. A. (J. Am. Chem. Soc., 1982)

(untitled) - Kitamura, M.; Koga, T.; Yano, M.; Okauchi, T. (Synlett, 2012)

(untitled) - Meguro, T.; Yoshida, S.; Hosoya, T. (Chem. Lett., 2017)

(untitled) - Stokes, B. J.; Opra, S. M.; Sigman, M. S. (J. Am. Chem. Soc., 2012)

(untitled) - Thiraporn, A.; Rukachaisirikul, V.; Iawsipo, P.; Somwang, T.; Tadpetch, K. (Eur. J. Org. Chem., 2017)